Molecular characterization of an adenovirus 3-16 intertypic recombinant isolated in argentina from an infant hospitalized with acute respiratory infection - Kajon, Adriana E. (2010)
An intertypic recombinant adenovirus with a serotype 3-like hexon gene and a serotype 16-like fiber (99% identical to that of the prototype strain of human adenovirus 16 [HAdV-16], Ch79) was isolated in Argentina from an infant admitted to the hospital with acute respiratory disease. Consistent with the results of molecular characterization, strain Arg827/04 was designated H3-F16. Copyright © 2010, American Society for Microbiology. All Rights Reserved.